Survey data on cost and benefit analysis for climate-smart agricultural (CSA) in the Coastal Savannah Agro-ecological Zone of Ghana - Karanja Ng'ang'a, Stanley; Mwungu, Chris Miyinzi; Miller, Vail; Essegbey, George Owusu; Karbo, Naaminong; Botchway, Vincent Ansah; Nautsukpo, Delali; Kingsley, Sam; Girvetz, Evan Hartunian (International Center for Tropical Agriculture, 2018)
This repository contains survey data on cost-benefit analysis of climate-smart agricultural practices in Coastal Savannah Agro-ecological Zone of Ghana. The data is organized in tables using Microsoft Excel. The Tables contains general information, site characteristics, household respondents type, the trend in physical productivity for the business as usual practice and the climate-smart agricultural practices. The data contained in the tables also contains the changes in the costs (i.e., maintenance, operation, and implementation cost). The major subject covered include climate-smart agricultural practices and cost and benefits analysis. The major objective of this study that the principal investigator attempted to answer is; to evaluate the main cost and benefits associated with implementing eight selected CSA practices in the coastal Savannah (AEZ) of Ghana (2018-06-11)